EFEKTIFITAS CONSTRUCTED WETLANDS TIPE SUBSURFACE FLOW SYSTEM DENGAN MENGGUNAKAN TANAMAN Cyperus rotundus UNTUK MENURUNKAN KADAR FOSFAT DAN COD PADA LIMBAH CAIR LAUNDRY - Eucenda Erwin P.; Tri Joko; Hanan Lanang D. (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The increased number of laundry industries in urban areal inflicted increase amount of detergent usage. Laundry’s liquid waste contains high phosphate and COD concentration that causing the water pollution. One of methods to reduce phosphate and COD is using constructed subsurface flow wetlands with Cyperus rotundus plant. The aim of this experiment is to determine the efectivity of retention time along 2, 4, 6, and 8 days to decreasing of phosphate and COD. The type of research is quasi experiment research with nonrandomized prestest posttest design, with amount of 48 samples. The samples were tested on Health Laboratory of Central Java Province. The results showed that the persentation to reduce phosphate with retention time of 2, 4, 6 and 8 days in a row are 76,06%, 82,24%, 64,39% dan 70,41%. The persentation to reduce COD with retention time of 2, 4, 6, and 8 days in a row are 88,84%, 94,79%, 83,98% dan 84,52%. The result of One Way Anova test showed that significance value of phosphate and COD in a row are (p-value) = 0,224 (p>0,05) dan (p-value) = 0,001 (p<0,05). The most effective of retention time to reduce phosphate and COD is 4 days. It was concluded that COD was appropriate quality standards, while phosphate was not appropriate quality standards. The further experiments needed to do with the variation in plant weight and number of plants.